Psychometric properties comparison among diverse versions of the invalidation childhood environmental scale (ICES) in Peruvian adults - Okumura-Clark, Alvaro (2024)
Introduction: The current tendency regarding psychometric assessment is to use brief versions of measurement tools. Objective: The present study sought to compare the psychometric properties of various versions in the length of the Invalidating Children Environment Scale (ICES). Method: Three hundred and twelve Peruvian university students participated as a sample. Confirmatory factor analysis was performed, and internal consistency was considered the reliability method. Results: The proposal with the best-fit indices was the brief version with nine items compared to the original version (14 items). Adequate internal consistency coefficients were determined for the scale factors. Finally, convergent and divergent validity were obtained through significant associations with the constructs of anxiety and depression. Conclusion: Various versions of the ICES comply with current psychometric standards, and the brief version of nine items is the most recommended.